(untitled) (Current Science Research Bulletin, 2025)
The modern development of physical culture and sports in Ukraine requires highly qualified specialists who combine theoretical knowledge with practical skills, innovative thinking, and the ability to adapt to modern challenges. However, the system of training such specialists today faces several serious problems. Among them are outdated curricula, insufficient practical training, and a gap between the labor market requirements and graduates' actual competencies. Training specialists in this field is a complex multifaceted process that requires a comprehensive analysis. It is essential to consider both the theoretical foundations of professional training and the practical application of knowledge and the integration of modern technologies into the educational process. Particular attention should be paid to the compliance of training programs with international standards, the availability of high-quality sports infrastructure, and innovative training methods. The analysis of modern research has shown that the problems of training specialists are considered in several key areas: the formation of comprehensive readiness of athletes, including psychological, physical, and technical training; modern methods of the training process, such as individualization of loads and biomechanical analysis of movements; technical support – introduction of interactive simulators and systems for monitoring the condition of athletes; the use of digital technologies in modern training of specialists. Based on the analysis, several priority areas for the development of the system of training specialists have been identified: modernization of the educational and material base, including the renovation of sports halls and the purchase of modern equipment, the improvement of coaching education through the introduction of interdisciplinary programs and the organization of internships abroad, the participation of students in sports competitions, the development of cooperation with professional federations and support youth sports initiatives, attention to the development of sports sciences in the field of physiology, biomechanics and sports medicine.